KINERJA KEBIJAKAN TENTANG PENGEMBANGAN USAHA BATIK DI KABUPATEN SIDOARJO - Endang Indartuti; Achmad Syafi’i (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2015)
The Performance of Batik Enterprise Development Policies in SidoarjoBatik is one of the Indonesia characteristics and cultural heritages. It is the Government’s responsibility to develop batik in accordance with the local characteristics of each region. At the same time, it is the opportunity for the batik producers around the archipelago to utilize the moment. The purpose of these activities are: the procurement of printing equipment and a table cap in accordance with the desired design pattern; skills training using the tool, with the direct learning methods applied; training and helping for business management and simple bookkeeping; assisting the marketing process through training techniques and marketing strategy; making the media marketing. The applied methods are: identifying the problem and needed equipment, such as: a molding tool/ stamp, tasting table for batik, stove to the tasting table, printer wok batik; skills training in using the tools, forming the simple bookkeeping, making media marketing. The taken approach is a direct method of learning and working with participatory methods. Results and implications: the procurement of 4 printing tools following the pattern of SMEs, provision of 2 sets consisting of: Tables stove, printer wok, gas stove, regulator, gas hose, 12 Kg LPG Tube, a marketing tool. They have been handed over to the SMEs. It had been done the technical training activities and business management training and simple bookkeeping. The existence of tools increase the number of batik production more than ever.Keyword: conservation, creativity, productivity, motif, batik